Analysis of the relationship between genomic instability, heterozygosity levels and phenotype in Saccharomyces cerevisiae - Sampaio, Nadia Maria Vieira, author; Argueso, Juan Lucas, advisor; Stargell, Laurie A., committee member; McKay, John K., committee member; Reardon, Kenneth F., committee member (Colorado State University. Libraries, 2018)
Understanding the forces that mediate genome evolution is a central problem in genetics, with implications for diverse processes that range from speciation, to biotechnological applications, to human disease. The central theme of my dissertation was the characterization of two forces, genomic instability and natural selection, that significantly impact genome structure by influencing the levels of genomic heterozygosity. While genomic instability processes can act to erode heterozygosity from the genome, natural selection may favor the maintenance of heterozygous alleles in cases where there is a positive correlation between heterozygosity and higher fitness. In Chapter I, I reviewed different types of mitotic mutations that can result in the appearance of tracts of homozygosity in genomes and recent discoveries about the temporal accumulation of such events. I also introduce the concept of heterosis, a phenomenon characterized by a positive correlation between genomic heterozygosity and phenotype in many species, and its potential role in contributing to the long-term maintenance of genomic heterozygosity. In Chapter II, I describe the characterization of a mechanism of systemic genomic instability in yeast that challenges the conventional model of gradual and independent accumulation of mutations. We showed that a subset of mitotic cells within a population experience bursts of genomic instability, which results in multiple independent events of loss-of-heterozygosity (LOH) accumulating over one or a few generations of mitotic cell division. We named this outcome "systemic genomic instability". The occurrence of this phenomenon was initially identified in the heterozygous yeast strain JAY270, and then validated in a conventional laboratory strain background, whose genome is almost fully homozygous. Elevated rates of coincident LOH was also observed in mutant strains incapable of entering meiosis, indicating cryptic initiation of meiotic recombination followed by return-to-growth in a few cells in the population was not responsible for the higher than expected rates of coincident LOH. This finding brings to light a novel and intriguing mechanism of genomic instability in yeast that has relevant parallels to bursts of accumulation of copy number alterations in the human genome, providing a powerful experimental model system to dissect the fundamental mechanisms responsible for the generation of rapid changes in chromosome structure. In Chapter III, we explored the role that genomic heterozygosity plays on the superior industrial traits of the JAY270 strain. In the previous Chapter we showed that mitotic recombination leading to LOH occurs at a high frequency during JAY270's clonal propagation. These LOH events act against the long-term maintenance of genomic heterozygosity, yet about 60% of JAY270's genome has remained heterozygous over time. We hypothesized that specific heterozygous alleles may have a positive impact on the traits of this strain and therefore were maintained through selection. We generated a collection of inbred strains derived from JAY270, and assessed them phenotypically under different growth conditions. Our results demonstrated that genomic heterozygosity indeed has a substantial impact on two important industrial traits of this strain – heat stress tolerance and growth kinetics. We identified several genomic regions potentially associated with those traits and conducted experiments to investigate the bulk contributions of heterozygosity blocks in three specific chromosomes. This study revealed candidate regions containing loci that potentially underlie important industrial traits of JAY270 and details on the extent to which heterozygosity may impact JAY270's genome evolution and phenotype. The combined results of these research projects provide important insights about the role of genomic instability mechanisms and their phenotypic outcomes in determining genome evolution, contributing discoveries that may have important practical implications for diverse fields, including biotechnology, cancer development and evolution, as well as genome sciences.
Keywords: heterozygosity; loss-of-heterozygosity; genome instability; industrial yeast strains; Saccharomyces cerevisiae